Enhanced Recovery Care vs. Traditional Care in Laparoscopic Hepatectomy: A Systematic Review and Meta-Analysis - Zhou, Xueyin; Zhou, Xueyi; Cao, Jiasheng; Hu, Jiahao; Topatana, Win; Li, Shijie; Juengpanich, Sarun; Lu, Ziyi; Zhang, Bin; Feng, Xu; Shen, Jiliang; Chen, Mingyu (Frontiers in Surgery, 2022)
Background Enhanced recovery care could alleviate surgical stress and accelerate the recovery rates of patients. Previous studies showed the benefits of enhanced recovery after surgery program in liver surgery, but the exact role in laparoscopic hepatectomy is still unclear. Aim We aimed to perform a meta-analysis to evaluate the safety and efficacy of enhanced recovery after a surgery program in laparoscopic hepatectomy. Methods The relative studies from a specific search of PUBMED, EMBASE, OVID, and Cochrane database from June 2008 to February 2022 were selected and included in this meta-analysis. The primary outcomes included length of hospital stay, duration to functional recovery, and overall postoperative complication rate. The secondary outcomes included operative time, intraoperative blood loss, cost of hospitalization, readmission rate, Grade I complication rate, and Grade II–V complication rate. Results A total of six studies with 643 patients [enhanced recovery care (n = 274) vs. traditional care (n = 369)] were eligible for analysis. These comprised three randomized controlled trials and three retrospective studies. Enhanced recovery care group was associated with decreased hospital stay [standard mean difference (SMD) = −0.56, 95% confidence interval (CI) = −0.83 −0.28, p < 0.0001], shorter duration to functional recovery (SMD = −1.14, 95% CI = −1.92 −0.37, p = 0.004), and lower cost of hospitalization Mean Difference (MD) = −1,539.62, 95% CI = −1992.85 −1086.39, p < 0.00001). Moreover, a lower overall postoperative complication rate was observed in enhanced recovery care group [Risk ratio (RR) = 0.64, 95% CI = 0.51 0.80, p < 0.0001] as well as lower Grade II–V complication rate (RR = 0.55, 95% CI = 0.38 0.80, p = 0.002), while there was no significant difference in intraoperative blood loss (MD = −65.75, 95% CI = −158.47 26.97, p = 0.16), operative time (MD = −5.44, 95% CI = −43.46 32.58, p = 0.78), intraoperative blood transfusion rate [Odds ratio (OR) = 0.71, 95% CI = 0.41 1.22, p = 0.22], and Grade I complication rate (RR = 0.73, 95% CI = 0.53 1.03, p = 0.07). Conclusion Enhanced recovery care in laparoscopic hepatectomy should be recommended, because it is not only safe and effective, but also can accelerate the postoperative recovery and lighten the financial burden of patients.